2011
DOI: 10.1007/s00198-011-1846-0
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the external validation of FRAX

Abstract: Cohort studies that have evaluated the performance of FRAX need to be interpreted with caution and preferably re-evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 51 publications
1
62
0
Order By: Relevance
“…The question of a limited value of comparative studies, focusing on the validation of different fracture risk or probability calculators, was discussed in detail by Kanis et al in the recently published opinion paper [18]. But, regardless of all the presented criticisms, one should agree that the direct comparison of different calculators is still justified by the fact that those diagnostic tools are dedicated to the same practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The question of a limited value of comparative studies, focusing on the validation of different fracture risk or probability calculators, was discussed in detail by Kanis et al in the recently published opinion paper [18]. But, regardless of all the presented criticisms, one should agree that the direct comparison of different calculators is still justified by the fact that those diagnostic tools are dedicated to the same practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The FRAX algorithm generated an area under the ROC curve (AUC) value of 0.845 for female hip fracture and QFractureScores had a value of 0.89 for the same event. Using this data for a direct comparison of FRAX and QFractureScores may however not be appropriate due to the difficulties encountered in comparing AUCs between studies, particularly when adjustments have not been made for differences in major predictive factors such as age between studies [18]. Recent work in an independent UK and Irish based population using only CRFs indicated that FRAX and QFractureScores were reasonably well correlated (R=0.857) for hip fracture suggesting that both tools could be of value in primary care settings [19].…”
Section: A Comparison Of Frax and Qfracturescoresmentioning
confidence: 99%
“…In the discussion the authors indicate the importance of having coherent data and models 25 . Among these authors is John Kanis, one of the creators of the FRAX ® model and defender of the validity of this system against various criticisms it has received 26 . Thus, in the search for new options to improve the understanding of the epidemiology of osteoporosis in Spain and increase the options for strategic approaches to this pathology, we present the baseline risk of expected fractures in our cohort using the Spanish FRAX ® model, along with a comparative exercise by applying the models of other European countries.…”
Section: Discussionmentioning
confidence: 99%